2007
DOI: 10.1258/000456307781646030
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and disorders of water balance: the physiology and pathophysiology of vasopressin

Abstract: Disorders of water balance are a common feature of clinical practice. An understanding of the physiology and pathophysiology of the key endocrine regulator of water balance vasopressin (VP) is key to diagnosis and management of these disorders. Diabetes insipidus is the result of a lack of VP or (less commonly) resistance to the renal effects of the hormone. Diagnostic testing can clarify aetiology and direct appropriate management. VP production can be associated with hyponatraemia. A comprehensive assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 96 publications
1
71
0
3
Order By: Relevance
“…Although we have not measured arginine vasopressin levels, previous studies demonstrated that an increased serum osmolality or a decreased plasma volume stimulate the secretion of arginine vasopressin. 39,40 Therefore, the decreased urinary output in obese subjects in our study might be the consequence of their higher sodium levels and decreased plasma volume (that is, more dehydrated status) compared with lean counterparts.…”
Section: Discussionmentioning
confidence: 80%
“…Although we have not measured arginine vasopressin levels, previous studies demonstrated that an increased serum osmolality or a decreased plasma volume stimulate the secretion of arginine vasopressin. 39,40 Therefore, the decreased urinary output in obese subjects in our study might be the consequence of their higher sodium levels and decreased plasma volume (that is, more dehydrated status) compared with lean counterparts.…”
Section: Discussionmentioning
confidence: 80%
“…The relationship between sodium and vasopressin in the SIADH has been categorised into four main groups (A-D) (4). Type A represents a picture with seemingly random AVP secretion, type B represents a picture where there is a 'reset osmostat', type C indicates AVP secretion that appears to be fixed at inappropriately high levels under hypotonic conditions, but then increases normally when the osmolality exceeds the usual threshold values, and finally type D SIADH represents antidiuresis in the absence of AVP.…”
Section: Discussionmentioning
confidence: 99%
“…Free water excretion was assessed by water load test according to a standard protocol (4). In brief, an oral water load (20 ml/kg) was administered over 15 minutes.…”
Section: Assessment Of Free Water Excretion: Water Load Testmentioning
confidence: 99%
See 2 more Smart Citations